Preparation of magnesium Ferrite-Doped magnetic biochar using potassium ferrate and seawater mineral at low temperature for removal of cationic pollutants. (April 2022) - Wen, Qin; Chen, Yijia; Rao, Xin; Yang, Run; Zhao, Yiming; Li, Jihui; Xu, Shuying; Liang, Zhenyi
Graphical abstract: Highlights: An MgFe2 O4 -doped magnetic biochar was manufactured without additional base. Iron oxides and oxygen containing groups were simultaneously introduced. High adsorption capabilities were achieved for different cationic pollutants. Both carbon matrix and iron species collaborated with each other for the adsorption. Abstract: Magnetic biochar has captured a great interest for remediation of environment as an easily separable carbonous adsorbent. Herein, a highly adsorptive magnetic biochar was manufactured through seawater mineral and K2 FeO4 co-promoted pyrolysis of jackfruit peel at 300 °C for removal of different cationic pollutants, and characterized by element analysis, FTIR, SEM-EDS, XRD, XPS and so on. MgFe2 O4 was generated without external base and a 19.42 emu/g saturation magnetization was achieved. Simultaneously, iron oxides and oxygen containing groups were introduced. The magnetic biochar exhibited 61.30 mg/g, 129.61 mg/g, and 1238.30 mg/g adsorption capacities for Cu 2+, methylene blue (MB), and malachite green (MG) at 25 °C, respectively, and remarkably surpassed the corresponding pristine biochar. The adsorption of MB and MG was mainly realized by electrostatic interaction, hydrogen bonding, complexation, and π-π electron-donor–acceptor interaction, and that of Cu 2+ was attributed to electrostatic interaction, hydrogen bonding, and complexation.